Remittance, Institutions and Investment Volatility Interactions: An Intercontinental Analysis (2017)
Generating massive investment for growth and development has been one of the main policy goals of most economies around the globe. Countries, most especially developing ones, are highly susceptible to investment volatility owing largely to the fragile nature of their economies as well as weaknesses in terms of dysfunctional institutions. Therefore, sound economic management suggests the need to better understand possible sources for mitigating the adverse effects of investment volatility. Remittances have been identified as important capital flows which do a good job of dousing macroeconomic volatilities. It is on this basis that the study sought to uncover the causal relationship between remittances and investment volatility via the intermediating role of institutions. Using a panel of 70 countries and the system Generalized Method of Moments (GMM) estimator, three insightful outcomes come to the fore. First, remittances played countercyclical roles across the estimated regressions. Second, institutional quality had no significant role in mitigating investment volatility and lastly, the interactive terms of both remittances and institutions significantly mitigated the negative impacts of investment volatility with the exception of the political component of the institutional architecture. Policy suggestions are drawn based on our results.